Biogeochemical niche conservatism relates to plant species diversification and life form evolution in a subtropical montane evergreen broad‐leaved forest. Issue 12 (3rd December 2022) - Bai, Kundong; Zhou, Xuewen; Lv, Shihong; Wei, Shiguang; Deng, Lili; Tan, Yibo
Abstract: The evolutionary mechanisms underlying the biogeochemical niche conservatism in forests remain incompletely understood. Here we aimed to determine how the strengths of biogeochemical niche conservatism vary among elements and between life forms. We measured leaf concentrations of basal elements (C, N, P, K, Ca, and Mg) in a wide range of life forms in a subtropical montane evergreen broad‐leaved forest. We found that differences in life forms such as evergreen/deciduous woody species and herbaceous/woody species significantly affected leaf elemental composition. The significant phylogenetic signal was present in leaf C, N, K, and Mg concentrations but absent in leaf P and Ca concentrations in all species. These contrasting strengths of biogeochemical niche conservatism were best generated by Ornstein–Uhlenbeck processes toward optima. Woody species were evolutionarily selected to show lower optimal leaf N, P, and K concentrations and higher optimal leaf C, Ca, and Mg concentrations than herbaceous species. The number of optima varied from the least in leaf C concentration to the most in leaf Ca concentration, suggesting the stronger convergent evolution of leaf Ca concentration. The positions of optima toward the tips were more selected in woody species, suggesting the more frequency of species‐specific adaptations in woody species. The positions of optima were also selected at the nodes towards the species groupings from certain life forms (e.g., the group of 12 Polypodiales ferns in leaf Ca evolution and the group of three evergreen Theaceae species in leaf P evolution) that were converged to present similar leaf elemental composition. During the evolution of biogeochemical niche, strong correlations were found among leaf C, N, P, and K concentrations and between leaf Ca and Mg concentrations. In conclusion, the strengths of biogeochemical niche conservatism can vary among elements and between life forms due to the different tempo and mode of Ornstein–Uhlenbeck processes. Abstract : Our results show that biogeochemical niche conservatism relates to plant species diversification and life form evolution in subtropical forest plants. Furthermore, the strengths of biogeochemical niche conservatism varying among elements and between life forms might be mostly determined by the tempo and mode of OU processes.